Kemampuan Pemahaman Konsep Teks Eksposisi Berbantuan Kuis pada Google Form Siswa Kelas X SMA Muhammadiyah 1 Pekanbaru - Calista, Novia; Faizah, Hasnah; Permatasari, Silvia (PAKAR Pendidikan, 2024)
This study aims to determine the level of students' abilities in understanding the exposition text concept material. The exposition text is used by the researcher as the main reference for the discussion that will be studied from the perspective of students' understanding of the material presented by the teacher. The aim is to find out and describe the level of ability to understand the concept of quiz-assisted exposition text on Google Form for class X SMA Muhammadiyah 1 Pekanbaru. The subjects in this study were class X SMA Muhammadiyah 1 Pekanbaru using the Probability Sampling technique with the Simple Random Sampling type (random system). The sample in this study totaled 56 students obtained from the lottery system. The data used in this study are test results obtained by students through the Google Form quiz feature. The results of the calculations that have been carried out show the value of – t table < t count < + t table (-1.674 < 0.828 < + 1.674). Thus, H0 is accepted because the results of the hypothesis testing prove that the results of the student's ability test with a value of 77.07 exceed the alleged hypothesis value, namely with a minimum completeness criterion value of 75.